Pengaruh Kompetensi Auditor,Independensi, dan Tekanan Waktu terhadap Kualitas Audit Dengan Teknologi Informasi Sebagai Moderasi - Habbil, Maulana Zhynangda; Isthika, Wikan; Pamungkas, Imang Dapit; Purwantoro, Purwantoro (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2026)
This study aims to analyze the effects of auditor competence, auditor independence, and time pressure on audit quality, with information technology as a moderating variable, at public accounting firms in Semarang. This study employs a quantitative approach using primary data collected via questionnaires and analyzed using SPSS. The results indicate that auditor competence and auditor independence have a positive effect on audit quality, whereas time pressure has no effect. Furthermore, information technology does not moderate the effects of auditor competence, auditor independence, or time pressure on audit quality.